Availability and accessibility to internet facilities as determinants of effective editorial services in book publishing firms in Southwestern Nigeria (2022)
Internet facilities are crucial for effective performance of editors in the book Publishing firms, as such availability of internet facilities in Publishing firms and editors’ access to such available facilities are the fulcrum to editorial Services. It is in the light of this that this study examined availability and accessibility to internet facilities as determinants of effective editorial Services in book Publishing firms in Southwestern Nigeria. Survey design was adopted for the study, structured questionnaire titled "Availability and Accessibility to Internet Facilities by Editors" was the research instrument, while four research questions were asked. The study population was the 54 registered educational Publishing firms in Southwestern Nigeria, while the sample for the study were the 102 editors in 25 Publishing firms that were randomly selected. The data collected was analysed using percentages and Statistical mean. Findings revealed a strong link between access to internet facilities and effective editorial Services in book Publishing firms. The study, therefore, recommended that editors should be given improved access to the internet facilities to boost their performance and improve the fortune of the Publishing industry.